BUSINESS EDUCATORS’ PERCEPTION ON PRODUCING QUALITY ENTREPRENEURSHIP EDUCATION GRADUATES IN TERTIARY INSTITUTIONS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study was conducted to ascertain curriculum contents of entrepreneurshipeducation which are suitable and teaching methods/strategies that are effective for producingcapable entrepreneurs in tertiary institutions in Anambra state. A questionnaire was used tocollect data from 42 business educators who teach entrepreneurship education courses. Tworesearch questions and two hypothesis guided the study. Mean was used to answer theresearch questions, while t-test and ANOVA were used to test the hypotheses. The findings ofthe study indicated that business educators' in tertiary institutions in Anambra state perceivedthe curriculum content' of entrepreneurship education to be suitable for producing capableentrepreneurs, and the teaching methods/strategies as effective except for lecture method. Itwas therefore recommended among others that business educators should adopt hands-onpractical approach in teaching entrepreneurship education courses.